Match analysis and temporal patterns of fatigue in rugby sevens - Granatelli, G.; Gabbett, T. J.; Briotti, G.; Padulo, J.; Buglione, A.; D`Ottavio, S.; Ruscello, B. M. (The Journal of Strength and Conditioning Research, 2014)
Rugby sevens is a rapidly growing sport. Match analysis is increasingly being used by sport scientists and coaches to improve the understanding of the physical demands of this sport. This study investigated the physical and physiological demands of elite men's rugby sevens, with special reference to the temporal patterns of fatigue during match play. Nine players, 4 backs and 5 forwards (age 25.1 ± 3.1 years) participated during 2 "Roma 7s" international tournaments (2010 and 2011). All the players were at the professional level in the highest Italian rugby union, and 5 of these players also competed at the international level. During the matches (n = 15), the players were filmed to assess game performance. Global positioning system, heart rate (HR), and blood lactate (BLa) concentration data were measured and analyzed. The mean total distance covered throughout matches was 1,221 ± 118 m (first half = 643 ± 70 m and second half = 578 ± 77 m; with a decrease of 11.2%, p > 0.05, Effect Size [ES] = 0.29). The players achieved 88.3 ± 4.2 and 87.7 ± 3.4% of the HRmax during the first and second halves, respectively. The BLa for the first and second halves was 3.9 ± 0.9 and 11.2 ± 1.4 mmol/L, respectively. The decreases in performance occurred consistently in the final 3 minutes of the matches (-40.5% in the distance covered per minute). The difference found in relation to the playing position, although not statistically significant (p = 0.11), showed a large ES (n2 = 0.20), suggesting possible practical implications. These results demonstrate that rugby sevens is a demanding sport that places stress on both the anaerobic glycolytic and aerobic oxidative energy systems. Strength and conditioning programs designed to train these energy pathways may prevent fatigue-induced reductions in physical performance.